2015
DOI: 10.1523/jneurosci.2093-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Full-Length Form of theDrosophilaAmyloid Precursor Protein Is Involved in Memory Formation

Abstract: The APP plays a central role in AD, a pathology that first manifests as a memory decline. Understanding the role of APP in normal cognition is fundamental in understanding the progression of AD, and mammalian studies have pointed to a role of secreted APP␣ in memory. In Drosophila, we recently showed that APPL, the fly APP ortholog, is required for associative memory. In the present study, we aimed to characterize which form of APPL is involved in this process. We show that expression of a secreted-APPL form i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 62 publications
5
23
2
Order By: Relevance
“…As with other APP family proteins, insect APPL is subject to cleavage by a combination of α, β, and γ-secretases (Figures 1G–J), consistent with the identification of all three secretase classes in multiple insect systems (Luo et al, 1990; Ramabhadran et al, 1993; Fossgreen et al, 1998; Greeve et al, 2004; Groth et al, 2010; Bolkan et al, 2012; Prussing et al, 2013; Pace et al, 2014; Bourdet et al, 2015; Lavore et al, 2015; Zheng et al, 2015). Likewise, our studies showed that Manduca APPL is preferentially cleaved by α-secretases under normal circumstances, as previously reported for both Drosophila APPL and human APP 695 (Haass et al, 2012; Wentzell et al, 2012; Zhang et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As with other APP family proteins, insect APPL is subject to cleavage by a combination of α, β, and γ-secretases (Figures 1G–J), consistent with the identification of all three secretase classes in multiple insect systems (Luo et al, 1990; Ramabhadran et al, 1993; Fossgreen et al, 1998; Greeve et al, 2004; Groth et al, 2010; Bolkan et al, 2012; Prussing et al, 2013; Pace et al, 2014; Bourdet et al, 2015; Lavore et al, 2015; Zheng et al, 2015). Likewise, our studies showed that Manduca APPL is preferentially cleaved by α-secretases under normal circumstances, as previously reported for both Drosophila APPL and human APP 695 (Haass et al, 2012; Wentzell et al, 2012; Zhang et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…Like APP, APPL is subject to proteolytic processing by α, β, and γ-secretases that generate an analogous spectrum of cleavage fragments, including sAPPs, CTFs, AICDs, and an Aβ-like peptide (Luo et al, 1995; Greeve et al, 2004; Carmine-Simmen et al, 2009; Poeck et al, 2012). Also like mammalian APP, APPL plays important roles in the developing nervous system, participating in the control of neuronal migration and synaptic plasticity (Torroja et al, 1999; Ashley et al, 2005; Ramaker et al, 2013; Soldano et al, 2013; Bourdet et al, 2015). Notably, studies in Drosophila have shown that defects caused by the loss of APPL can be rescued by the expression of human APP 695 (Luo et al, 1992; Wentzell et al, 2012), indicating that these proteins are both structurally and functionally homologous.…”
Section: Introductionmentioning
confidence: 99%
“…APPL silencing in the MB of adult flies was shown to disrupt MTM and LTM, but neither learning nor ARM formation was affected (Goguel et al, 2011; Bourdet et al, 2015b). MTM and LTM are two memory phases known to share identical neuronal circuits (Bouzaiane et al, 2015), indicating a role for APPL in these structures.…”
Section: Appl Is Required For Specific Memory Phasesmentioning
confidence: 99%
“…Consequently, APPL sd is exclusively expressed as a transmembrane protein. Overexpression of APPL s in the adult MB rescued the MTM deficit caused by a reduction of endogenous APPL levels, indicating that a secreted fragment of APPL is involved in memory (Bourdet et al, 2015b). This is consistent with mammalian studies showing a role for sAPPα in memory (Meziane et al, 1998; Bour et al, 2004; Ring et al, 2007; Taylor et al, 2008).…”
Section: Appl Is Required For Specific Memory Phasesmentioning
confidence: 99%
See 1 more Smart Citation